Dictionary of Qumran Aramaic - Cook, Edward M. (Eisenbrauns, 2015)
Introduction; Acknowledgments; Abbreviations; א; ב; ג; ד; ה; ו; ז; ח; ט; י; כ; ל; מ; נ; ס; ע; פ; צ; ק; ר; ש;ׁ שׂ; ת; Bibliography of Works Cited.